(untitled) (Dhaka University Journal of Science, 2023)
The simulations of Severe Cyclonic Storm (SCS) Mora (28-31 May 2017) generated over the Bay of Bengal (BoB) are performed in this study to analyze its features, landfall, and track using the Weather Research and Forecasting (WRF) model. WRF-ARW model has been used on a 10 km Horizontal Resolution (HR) domain for 96, 72, 48, and 24-hour lead time simulations. The model’s performance is assessed by examining Mean Sea Level Pressure (MSLP), vertical distribution of velocity components, wind flow pattern, relative vorticity, vertical wind shear, relative humidity, latent heat flux at the surface, and track pattern. The simulated results are compared carefully to the observations from the Bangladesh Meteorological Department (BMD) and the India Meteorological Department (IMD). The findings are reasonably consistent with the observations. The simulated track is also reasonable even up to 72 hours in advance. Finally, the study’s results suggest that the WRF model can be used as an effective tool in predicting TCs over the BoB. Dhaka Univ. J. Sci. 71(2): 142-152, 2023 (July)